STUDI DESKRIPTIF TERHADAP REGULASI EMOSI PADA SISWA KELAS IX DI SMP NEGERI 2 PAKISJAYA - Rizky Lazuardi Nuz'amidhan; Ecep Supriatna; Reza Pahlevi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
Emotion is a volatile state in an individual that functions or acts as an internal adjustment to the environment to achieve individual well-being and safety. Emotion regulation is the ability of students to control, evaluate and modify their emotions. Students who have high or stable and normal emotional regulation are able to regulate their emotions and can express emotions in accordance with the norms and circumstances of the surrounding environment.The method used is a descriptive method with a quantitative approach and the subjects in this study were students of SMP Negeri 2 Pakisjaya Determination of the sample size taken using the Slovin formula as many as 120 students. The sampling technique used in this study is Proportional Random Sampling, it is intended that each population in the class can represent. The results showed that the majority of students' emotional regulation were in the moderate category, amounting to 88 (73.33%), for the high category there are 12 (10%), and the remaining 20 (16.67%) are in the low category.It was concluded that the majority of the students of SMP Negeri 2 Pakisjaya were in the moderate category and had normal and stable emotional regulation. Keywords: : Emotional Regulation, Learners